Archaeal LOV domains from Lake Diamante: first functional characterization of a halo-adapted photoreceptor - Valle, Lorena; Coronel, Yonathan J.; Bravo, Guillermina E.; Díaz, Joaquín A.; Albarracín, Virginia Helena; Farías, María E.; Abatedaga, Inés (Frontiers in Microbiology, 2025)
High-altitude Andean lakes (HAALs) represent polyextreme environments where diverse photoinduced processes have been documented. In this study, we investigated Light-Oxygen-Voltage (LOV) photoreceptors and identified 28 archaeal sequences from Lake Diamante, which were classified into two major groups (A and B), with three outliers showing unique structural features. Analysis of these sequences and their 3D models revealed hallmark adaptations to halophilic environments, including an abundance of surface acidic residues, an increased prevalence of arginine over lysine, and a greater density of salt bridges. The heterologous expression of a representative LOV domain, ALovD-1, demonstrated conserved photophysics between its dark- and light-adapted states, which was consistent with the slow cycling type. Importantly, ALovD-1 exhibited remarkable halophilic characteristics, maintaining photocycling functionality at salt concentrations as high as 3 M monovalent salts. This ability can be attributed to discrete structural changes, allowing adjustments in flavin interactions within its cavity under varying ionic strengths. Mutational studies of key residues (Y30F and Y48F) highlighted their roles in modulating flavin photophysic and revealed a stabilizing function for Y48 at low salt concentrations. These findings mark the first functional characterization of a canonical archaeal LOV domain, expanding our understanding of light sensing and protein adaptation in extremophiles.